(untitled) - Carey, Francis A. (New York, 2007)
This volume assumes a level of familiarity with structural and mechanistic concepts comparable to that in the companion volume, Part A, Structures and Mechanisms. Together, the two volumes are intended to provide the advanced undergraduate or beginning graduate student in chemistry with a sufficient foundation to comprehend and use the research literature in organic chemistry
Keywords: Chemistry, Organic,Hóa học, hữu cơ